Explaining contextual factors affecting e-commerce adoption progression in selected SMEs: evidence from Botswana. (2013) - Shemi, Alice P.; Procter, Chris
This paper provides an interpretive account of contextual factors that affect the progression of e-commerce in six Small and Medium Enterprises (SMEs) in a developing country context of Botswana. The methodology followed multiple in-depth case studies, using semi-structured face-to-face interviews, website analysis, observation and document analysis. Results show that contextual factors peculiar to each SME provide better explanations on how SMEs progress in e-commerce adoption. At the high level of adoption, managerial innovativeness and the nature of the external e-commerce market has contributed to success in two SMEs, whereas the local business environment in combination with some organisational factors can explain the low-level and non-adoption in the other four SMEs. Future implications indicate that managers need to pay particular detail to the unique and idiosyncratic nature of SMEs in guiding decisions for e-commerce adoption in their firms.